A Lymph Node Count-Based AJCC Staging System Facilitates a More Accurate Prediction of the Prognosis of Patients With Endometrial Cancer - Huo, Xinlong; Wang, Shufang (Frontiers in Oncology, 2021)
Purpose: Both the International Federation of Gynecology and Obstetrics (FIGO) and the American Joint Committee on Cancer (AJCC) staging system for endometrial cancer (EC) defined the N category by the location of metastatic lymph nodes (LNs) rather than the metastatic LN count. We aimed to compare the accuracy of the AJCC staging system and the LN count-based staging system. Patients and methods: EC patients were selected from the Surveillance, Epidemiology and End Results (SEER) database between 2004 and 2016. Patients’ characteristics were collected, including age, race, marital status, histological type, grade, therapeutic measures, the number of metastatic LNs, the number of dissected LNs, vital status, and survival in months. Overall survival (OS) was analyzed by the Kaplan–Meier (KM) method and the concordance index (C-index) was used to compare the prognostic value of the AJCC staging system and the LN count-based staging system. Results: We identified 4,276 EC cases from the SEER database, including 2,693 patients with stage IIIC1 and 1,583 patients with stage IIIC2. Multivariate analyses showed that independent prognostic factors for patients with stage IIIC1 included age, race, marital status, grade, histology, chemotherapy, and radiotherapy. Independent prognostic factors for patients with stage IIIC2 included age, marital status, grade, histology, chemotherapy, and radiotherapy. The C-index of the AJCC staging system and the LN count-based staging system were 0.483 and 0.617, respectively. At least six LNs should be dissected to ensure the accuracy of the LN count-based staging system. Conclusion: A modified AJCC staging system based on the count of metastatic LNs might be superior to the current AJCC staging system, which still had room for improvement and further refinements were required. For accurate staging, we recommended that at least six LNs should be examined in the modified AJCC staging system.